Benzophenone 1 induced photogenotoxicity and apoptosis via release of cytochrome c and Smac/DIABLO at environmental UV radiation. Issue 3 (15th December 2015) - Amar, Saroj Kumar; Goyal, Shruti; Dubey, Divya; Srivastav, Ajeet K.; Chopra, Deepti; Singh, Jyoti; Shankar, Jai; Chaturvedi, Rajnish K.; Ray, Ratan Singh
Graphical abstract: Highlights: Role of Smac/DIABLO in activation of caspase 3. Caspase 3 dependent apoptosis via mitochondrial pathways. Photosensitized BP1 induced DNA damage, micronuclei and CPDs formation. Role of cytochrome c and Apaf 1 in apoptosis. Photogenotoxic potential of BP1 in HaCaT cells at environmental UV radiation. Abstract: Solar UV radiation is main factor of photocarcinogenesis, photoageing, and phototoxicity; thus, protection from UV radiation is major concern. Sunscreens containing UV filters are suggested as sun safe practices, but safety of UV filters remains in controversies. Benzophenone-1 (BP1) is commonly used in sunscreens as UV blocker. We assessed the photogenotoxicity and apoptotic parameters in human keratinocytes (HaCaT cells) by western blot, immunocytochemistry, flowcytometry, comet assay and TEM imaging. Our results exposed that BP1 photosensitized and generated intracellular ROS (2.02 folds) under sunlight/UVR. Decrease in cell viability was recorded as 80.06%, 60.98% and 56.24% under sunlight, UVA and UVB, respectively. Genotoxic potential of BP1 was confirmed through photomicronuclei and CPDs formation. BP1 enhanced lipid peroxidation and leakage of LDH enzyme (61.7%). Apoptotic cells were detected by AnnexinV/PI staining and sub G1 population of cell cycle. BP1 induced up regulation of apoptotic proteins Bax/Bcl2 ratio, Apaf-1, cytochrome c, Smac/DIABLO and cleaved caspase 3 was noticed. Down regulation of pro caspase 3 was inhibited by Z-VAD-fmk (inhibitor of caspase). Thus, study established the involvement of BP1 in photogenotoxicity and apoptosis via release of cytochrome c and Smac/DIABLO. These findings suggest sunscreen user to avoid BP1 in cosmetics preparation for its topical application.